Freedom of Religion among Muslim Minority in Secular State: A Case Study in the Philippines - Guleng, Marlon Pontino; Muhamat@Kawangit , Razaleigh; Usman, Abur Hamdi (International Journal of Psychosocial Rehabilitation, 2020)
The survival of Islamic da’wah in the Philippines is need to come up with the comprehensive programs which enhance the Muslims society to survive into the current critical condition under the Philippine constitution that promotes secularism. This research aims to analyze the impacts Islamic da’wah activities in the Philippines. In this study, a quantitative methodology research was applied which include a survey of a set of questionnaires to the total number of respondents as of 272 people and the data were analyzed using Statistical Package for the Social Sciences (SPSS) for Windows version 21. The results showed the impacts of Islamic da’wah activities which mainly focus on the freedom of religion and acceptance of Islam as a way of living in Cordillera Administrative Region gave the high level of mean values of 4.07 and 3.81 respectively. The results found that there is an increasing of number of Christians accepting Islam as their new religion in life.